2022
DOI: 10.1155/2022/8495996
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Cardiopulmonary Rehabilitation Promotion Mode Intervention Combined with Oxygen Therapy on Cardiopulmonary Function and Blood Gas Analysis Indexes of COPD Patients with Cor Pulmonale

Abstract: Chronic obstructive pulmonary disease is a common respiratory disease. This paper observes the effects of cardiopulmonary rehabilitation promotion mode intervention combined with oxygen therapy on cardiopulmonary function and blood gas analysis indexes in patients with chronic obstructive pulmonary disease (COPD) complicated with cor pulmonale. A total of 136 COPD patients with cor pulmonale admitted to our hospital from July 2018 to October 2020 were selected as the research objects and divided into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%